THE EFFECTIVENESS OF COGNITIVE BEHAVIORAL THERAPY (CBT) IN THE TREATMENT OF ALCOHOL USE DISORDER (AUD) – A COMPREHENSIVE REVIEW - Michal Ziemba; Klaudia Zackiewicz; Agata Wińska; Oliwia Sędziak; Hanna Pietruszewska; Agata Ogórek; Irmina Czerepak; Paweł Liszka; Katarzyna Kleszczewska; Izabela Majchrzak (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Alcohol use disorder (AUD) drives preventable illness and death worldwide, causing medical, mental health, and social harms that strain individuals and health systems. Cognitive behavioral therapy (CBT) targets maladaptive cognitions, conditioned cues, and high risk situations using functional analysis, coping skills training, and relapse prevention grounded in learning and cognitive theory. Relapse prevention frameworks emphasize high risk situations, coping responses, outcome expectancies, abstinence violation effects, and covert antecedents (e.g., urges) to enhance self efficacy and reduce relapse, with meta analyses showing benefits over minimal or non specific controls. Effects versus non specific therapies are small but significant early and generally attenuate over time, while head to head comparisons show comparable efficacy, highlighting maintenance care, treatment matching, and mechanism focused augmentation. Technology delivered CBT expands access and can reduce consumption and increase abstinence, with early trials suggesting noninferiority or advantages over clinician delivered CBT, warranting larger, longer evaluations and careful integration with pharmacotherapy in stepped care. Study overview and methodology: This review examined randomized controlled trials evaluating CBT efficacy for substance use disorders, primarily alcohol. Studies compared CBT against three types of controls: minimal treatment, non-specific therapy, and specific evidence-based therapy. Effect sizes were pooled using inverse-variance weighting under random effects assumptions, with outcomes assessed at both early and late follow-up periods for frequency and quantity measures. Conclusion: Cognitive behavioral therapy is a reliable, evidence-based option for alcohol use disorder that achieves meaningful reductions in drinking and supports maintenance of gains, performing on par with other established therapies; its emphasis on relapse prevention skills and flexible delivery, including effective digital formats, makes it well suited for integration into comprehensive, stepped-care models tailored to individual needs.